Emergency Medical Service (EMS) systems on the world and the Polish system - Kosydar-Bochenek, Justyna; Ozga, Dorota; Szymańska, Jolanta; Lewandowski, Bogumił (Polish Journal of Public Health, 2012)
Modern emergency medical service in the world is a new discipline, which counts only a few years. The process of creating an emergency medical service system (EMS) is long and difficult. It requires experience and cooperation of many groups: medical, administrative and political. In the history of the formation of system solutions in emergency medical services and emergency medicine there are two system models: the Franco-German (FSG) and the Anglo-American (AAS). Models owe their names to countries where the ideas of systems born and developed over the years. Today, most EMS systems around the world have varied composition from each model. Another way to classify emergency medical service systems is according to the level of service and scope of practice provided. There are usually classified as a Basic Life Support (BLS) level and Advanced Life Support (ALS) level. Poland for several years definitely moving towards a model of Anglo-American. Emergency medicine and emergency medical services are inextricably related to saving lives and health, and they undeniable development occurred in the late twentieth and early twenty-first century. In Poland they are among the specialities priority because of their intensive development is not only survival, but also the quality of life of victims depends.